PEMETAAN POTENSI KOMODITAS HORTIKULTURA UNGGULAN DI KOTA BATU - Sika; Mubarokah, Mubarokah; Priyanto, Eko (Universitas Djuanda, 2023)
Horticulture is the agricultural subsector that is mostly occupied by farmers, this can be seen from the amount of land use for horticulture which is more dominant than other agricultural subsectors, according to the Department of Agriculture and food security, the horticulture sector has a planting area of ​​6449,758 hectares with a total area of ​​6449,758 hectares. As many as 71 horticultural commodities are cultivated, Batu City is one of the areas in East Java that relies on the agricultural sector for its economic development, but Batu City does not yet have a clear picture of the specifications for leading commodities, especially the horticulture sub-sector. The analytical tool that can be used to determine base and non-base commodities is Location Quotient (LQ) analysis, while the tool used to classify the growth of each commodity can use Shift Share Analysis (SSA), then the results of the two analyzes are combined with the Batu City geographic map using the technique Overlay so as to produce a map of Batu City's leading commodities. With the focus of research on every sub-district in Batu City, this is because the sub-district is an integral part of the city.